Meningkatkan Hasil Belajar Matematika dengan Menerapkan Model Pembelajaran Berbasis Masalah (Problem Based Learning) pada Pokok Bahasan Luas Permukaan Prisma dan Limas di Kelas X SMKN 1 Idanotae Tp.2022/2023 - Lubin Johannes Siahaan (Journal on Education, 2024)
Improving Mathematics Learning Outcomes by implementing a Problem Based Learning model on the subject of surface area of ​​prisms and pyramids in Class X of SMK Negeri 1 Idanotae. The research was prepared as a report on the implementation of PPL PPG Daljab class 3 2023 activities. Mathematics learning practices at SMK Negeri 1 Idanotae are still dominated by conventional learning where students are positioned as learning objects, students are considered not to know or understand anything, while teachers Position yourself as someone who has knowledge. So the teacher seems to have the highest authority in the learning process. This research aims to apply the Problem Based Learning (PBL) learning method so that there is an increase in student mathematics learning outcomes. The type of research carried out is Classroom Action Research (PTK) with data collection techniques through learning results test sheets. The subjects in this research were class X students of SMK Negeri 1 Idanotae. The results of this research show that the application of the Problem Based Learning (PBL) learning method can improve student mathematics learning outcomes. The increase in student learning outcomes can be seen from the increase in the average student score from Pre-cycle, cycle I to cycle II with a percentage of completeness, namely: 26%; 60%; 67%.